Optimasi Respon Elektrokimia Gliserol Berbagai Tingkat pH Studi Voltametri Siklik Dengan Elektroda Kerja Amalgam (Cu/Hg) - Mohammad Chabibur Rohman; Pirim Setiarso (Unesa Journal of Chemistry, 2024)
Effect of pH on glycerol measurement using Cu/Hg amalgam working electrode by cyclic voltammetry method. The Cu/Hg amalgam electrode was chosen for its good conductivity and ease of surface cleaning, which prevents passivation due to compound buildup on the surface. In this study, the working electrode, comparison electrode, and auxiliary electrode were dipped into a glycerol solution with a pH variation between 5 and 8. The results show that the optimum pH for glycerol measurement is pH 7, with the highest reduction current response of -0.0142 A, indicating optimal glycerol ionization conditions. The decrease in current response above pH 7 is due to the interaction of glycerol with phosphate buffer which shifts the reaction equilibrium towards the formation of a by-product, hydroxypropenal. Therefore, the Cu/Hg amalgam electrode is effectively used as a working electrode for glycerol analysis, with the optimum pH at 7 for maximum results